PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA EVITEL HOTEL DI KOTA BATAM - Msi, Dessy; Evyanto, Winda (LPPM Universitas Putera Batam, 2021)
The development of tourism in the city of Batam has increased very rapidly. There is more competition in service companies so that certain strategies are needed to survive in the market. Companies must maximize customer satisfaction in order to maintain the survival of the company. In achieving customer satisfaction, the company must pay attention to two variables, that is facilities and service quality. In this reserch to determine and analyze the effect of facilities and service quality on customer satisfaction at Evitel Hotel Batam. Because the facilites provided always not in accordance with customer satisfication, it makes customers think twice about visiting to stay again. In service quality, the lack of provided such as unfriendly staff aand lack of communicative between customers and the customer servce. In this reserch has a population of 14.580 customers. The sample used was a convenience sampling technique, in calculating the number of samples using the slovin formula with a sample of 100 Data collection technique in this study using a questionnaire. In this data processing method in this study uses SPSS 21. Based on the test result, the facilities and quality of service simultaneously has a positive and significant influence on customer satisfaction.